Evaluation of ovarian and testicular tissue cryopreservation in children undergoing gonadotoxic therapies - Babayev, Samir N. (Springer US, 2012)
OBJECTIVE: Ovarian and testicular tissue cryopreservation are the only fertility preservation options for sexually immature individuals. Because of their experimental nature, it is important to determine safety and possible bundling with other medicallyindicated procedures. STUDY DESIGN: Prospective observational. RESULTS: Cryopreservation indications included cancer in 75 % of females and 50 % of males, while non-cancer indications included various hematological conditions. Similar numbers of females (12/28) and males (3/9) underwent prior chemotherapy. Females underwent laparoscopic (27/28) or robotic (1/28) approaches while incisional biopsy was used in males. Bundling of ovarian and testicular harvesting with other medicallyindicated procedures was performed in 42 % and 22 %, respectively. The operative time inclusive of bundled procedures was similar (1.6 ± 0.1 vs. 0.9 ± 0.3 h) but the discharge time was significantly longer for females than males (10.4 ± 0.6 vs. 4.6 ± 0.6 h, p < 0.05) due to frequent bundling of medically-indicated procedures in females. All procedures were successfully completed without complications or significant blood loss. CONCLUSIONS: Pediatric gonadal tissue cryopreservation can be combined with other medically-indicated procedures to minimize the potential inconvenience, additional anesthetic risks, and costs.